Employee Privacy, Law and Practice - DECKER,KURT (Tufts Archival Research Center, 2007)
Employee Law and Privacy Practice report regarding smoking policies in the workplace. Mentions employee medical records and the rights to obtain these pieces of information. Includes information on smoker's rights within a workplace. Refers to vulnerability of a smoker in the workplace with rules and regulations.